352 Intra-operative frozen section examination of pelvic lymph nodes in early cervical cancer. (13th November 2020) - Jackson, E; Addley, S; Soleymani majd, H; Dhar, S; Alazzam, M
Abstract : Introduction: Frozen section examination (FSE) of pelvic lymph nodes in early stage cervical cancer is designed to avoid the morbidity of dual therapy. It is however timely and expensive. Method: All patients undergoing surgery for early stage cervical cancer between 2010–2019 in a UK tertiary centre were identified (n=180). All patients had pre-operative MRI scans performed and all patients underwent planned intra-operative FSE. Nodes retrieved by FSE were examined by expert pathologists. Patient MRI and histology findings were analysed to suggest an optimal approach to employing FSE. Results: 4913 lymph nodes in total were retrieved. 22/180 patients had positive nodes on FSE. 18 of these had intermediate/high grade tumours; and 13 had no suspicious lymph nodes identified on pre-operative MRI. The sensitivity of MRI to detect positive nodes was 40% (95% CI 20% to 63%); specificity 83% (95% CI 76% to 88%); NPV 91% (95% CI 88% to 94%); and PPV 25% (95% CI 16% to 39%). Conclusions: Pre-operative MRI did not reliably predict the presence of lymph node involvement in women with intermediate/high grade cervical cancer. Perhaps FSE could be targeted to this group, employing this timely and expensive technique in those at greatest risk having nodal disease.